2019
DOI: 10.1620/tjem.247.1
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of HIV-1 Drug Resistance among Patients with Antiretroviral Therapy Failure in Sichuan, China, 2010-2016

Abstract: Antiretroviral therapy (ART) has been introduced recently and has significantly impacted morbidity and mortality, but can also engender drug resistance. To identify the prevalence of HIV-1 drug resistance (HIVDR) among patients with antiretroviral therapy failure in Sichuan during the period from 2010 to 2016, we carried out a longitudinal study in Sichuan, a province with the highest HIV/AIDS prevalence in China. The data and blood samples were collected from HIV/AIDS patients who received ART for more than h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
21
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 21 publications
3
21
0
Order By: Relevance
“…In our case, the patient had M184 mutations conferring resistance to 3TC, emtricitabine (FTC), didanosine (ddI) and abacavir (ABC), while K65R causes intermediate to high-level phenotypic and clinical resistance to TDF, ddI, ABC and d4T and low level to intermediate phenotypic and clinical resistance to 3TC and FTC. Drug resistance surveillance of CRF01_AE subtype in a Chinese cohort experiencing ART failure reported occurrence of M184V and K65R mutations at 64.98% and 15.97%, respectively, among treatment failures 38. The M184 mutation is not a contraindication to a continued treatment with 3TC or FTC, thus 3TC remained a part of our patient’s ART regimen.…”
Section: Discussionmentioning
confidence: 73%
See 2 more Smart Citations
“…In our case, the patient had M184 mutations conferring resistance to 3TC, emtricitabine (FTC), didanosine (ddI) and abacavir (ABC), while K65R causes intermediate to high-level phenotypic and clinical resistance to TDF, ddI, ABC and d4T and low level to intermediate phenotypic and clinical resistance to 3TC and FTC. Drug resistance surveillance of CRF01_AE subtype in a Chinese cohort experiencing ART failure reported occurrence of M184V and K65R mutations at 64.98% and 15.97%, respectively, among treatment failures 38. The M184 mutation is not a contraindication to a continued treatment with 3TC or FTC, thus 3TC remained a part of our patient’s ART regimen.…”
Section: Discussionmentioning
confidence: 73%
“…INSTIs comprise a key drug class that has been shown in randomised controlled trials to be more effective in rapidly decreasing HIV viral load within 12 weeks when compared with the standard NNRTI and NRTI combinations,33 and this effect is similar across most INSTIs 33 34. Reports have shown an increasing numbers of pretreatment NNRTI resistance among ART-naïve patients35–37 and can be >25% among those experiencing ART failure 38. In our case, HIV genotyping revealed mutations in K101E and Y181C, causing resistance to EFV and Y181I/V mutations causing resistance to NVP, etravirine and rilpivirine.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The findings confirmed that the prevalence of virological failure on ART (41.81%) among PLWH was high in this area, which was higher than that in other high HIV epidemic areas of China (11.8%-17.5%) [22], and even higher than that in East and West Africa (9.1%-25.4%) [23][24][25]. The prevalence of drug-resistance was as high as 32.10%, which is lower than that of other places of Sichuan province (35.4%-50.7%) [21,26] and other HIV epidemic areas of China (50%-65%) [27,28]. A high prevalence of subtype CRF07_BC (95.62%) was observed among PLWH with virological failure on ART, which was different from other areas of China.…”
Section: Discussionmentioning
confidence: 74%
“…Moreover, 42.0%-86.2% of the HIV-infected individuals had at least one resistance mutation in Iran [5,9,20]. It was also reported in China that with the increase in the coverage of ART, drug resistance increased from 23.0% to 74.0% from 2010 to 2016 [35].…”
Section: Parametermentioning
confidence: 89%